The Impact of Inflation on the Financial Statements of Banks in Sudan: The Case Study of Bank(S (American Journal of Economics and Business Innovation, 2025)
The research examined the impact of inflation on the financial statements of banks in Sudan. The research problem was that ignoring the effect of the rise in the general level of prices (inflation) when preparing traditional (historical) financial statements leads to the inaccuracy and unreality of these lists and the decisions based on them, and their incomparability. The importance of the research stems from the fact that accounting information has become a strategic input into the decision-making process and, accordingly, its shortcomings and unrealism negatively affect decision-making related to investment and various economic development plans. The research aimed to study and know the impact of the rise in the general level of prices on the financial statements and to demonstrate the importance of these lists as a source of information for making rational decisions. The research relied on the descriptive and analytical approach to solve the research problem and achieve its objectives. The case of Bank (S) was studied, and it was concluded that there are fundamental differences between the numbers of the traditional financial statements and the numbers of the modified financial statements, which reflects the lack of validity and suitability of the traditional financial statements. The research reached a number of results, the most important of which is that: Preparing financial statements based on historical cost does not reflect the truthfulness and realism of the business results and financial position. It is not consistent with the concept of capital preservation. The research concluded with several recommendations, including the need to consider inflation’s impact when preparing financial statements.